(untitled) (Journal of the College of Basic Education, 2022)
This work involves study the corrosion behavior of amalgam in artificial saliva at pH=6 and 37oC after using Nd: YAG, where this laser used for healing the cancer. This study indicates that laser surface treatment affecting corrosion resistance of amalgam, and the results indicate that the laser treatment don`t give the desired purpose because the nature of amalgam and the presence of mercury in this alloy which may be evaporate and it give toxicity for human and the energy of treatment must be low to avoid evaporation. In this work, laser treatment with two pulses under experimental conditions gave little improvement in corrosion resistance of amalgam compared with one and three pulses through the corrosion parameters of polarization behavior